2017
DOI: 10.1007/s12178-017-9445-0
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative Scoliosis

Abstract: Purpose of Review The purpose of this review is to provide an updated review of adult degenerative scoliosis (ADS). Epidemiology, classification, pathophysiology, and natural history are discussed along with a summary of commonly used outcome measures. Operative vs non-operative outcomes and new surgical techniques are discussed. Recent Findings The SRS-Schwab classification (2012) combines clinical and radiographic evaluation including overall global alignment. Current evidence regarding risk factors and effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 59 publications
0
48
0
11
Order By: Relevance
“…45 Patients with degenerative lumbar scoliosis present at a relatively high age, often with several comorbidities and poor bone quality. 1,25,45,52 This increases the risk of intra-and postoperative complications, 15,21 which is shown by a study of Transfeldt et al, who reported a complication rate of 40%-56% after spinal fusion, compared to only 10% in decompression alone. 47 FIG.…”
Section: Discussionmentioning
confidence: 98%
“…45 Patients with degenerative lumbar scoliosis present at a relatively high age, often with several comorbidities and poor bone quality. 1,25,45,52 This increases the risk of intra-and postoperative complications, 15,21 which is shown by a study of Transfeldt et al, who reported a complication rate of 40%-56% after spinal fusion, compared to only 10% in decompression alone. 47 FIG.…”
Section: Discussionmentioning
confidence: 98%
“…The patient suffers from breathing difficulty; digestive disorders are common and promote abdominal hypertension and sphincter disorders. The loss of lumbar lordosis has multiple causes: a decrease in the anterior height of the disc, hypertrophy of the facet joints and spinous process increasing the posterior height, and loss of extensors muscle strength [29].…”
Section: Discussionmentioning
confidence: 99%
“…A associação com laterolistese é frequente, sendo ocasional a presença de curvas torácicas compensatórias. 10 Quando comparada com a EIA, a escoliose de novo apresenta curvas com menor angulação, entretanto com maior progressão (1,64°/ano versus 0,82°/ano). 17 A EIA ocorre em indivíduos com escoliose preexistente, principalmente do sexo feminino, em dois padrões principais.…”
Section: Apresentação Clínicaunclassified
“…Os parâmetros espinopélvicos, a lordose lombar e cifose torácica também devem ser avaliados. 10 À análise radiográfica, o aumento da rotação da vértebra apical (3 de Nash-Moe), ângulos de Cobb > 30°, assimetria dos discos intervertebrais acima e abaixo da vértebra apical, laterolistese > 6 milímetros, linha interilíaca (linha entre os aspectos superiores de ambas as cristas ilíacas) seccionando L5 ao invés de L4 são preditivos de progressão da curva. Já a presença de osteófitos anteriores confere maior estabilidade à coluna vertebral.…”
Section: Avaliação Radiográficaunclassified
See 1 more Smart Citation